Proceedings of the 2nd ACM International Workshop on IoT Privacy, Trust, and Security 2016
DOI: 10.1145/2899007.2899008
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Security and Privacy of Cloud-based Video Surveillance Systems

Abstract: In the area of the Internet of Things, cloud-based camera surveillance systems are ubiquitously available for industrial and private environments. However, the sensitive nature of the surveillance use case imposes high requirements on privacy/confidentiality, authenticity, and availability of such systems. In this work, we investigate how currently available mass-market camera systems comply with these requirements. Considering two attacker models, we test the cameras for weaknesses and analyze for their impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 5 publications
0
42
0
Order By: Relevance
“…For example, research has shown that-by taking advantage of hardware or protocol flaws-attackers can exploit man-in-the-middle attacks to intercept communications from and to wearable devices to steal personal information, invading user's privacy and exposing them to the risk of identity theft [7]. Attackers can also take advantage of the weak authentication and encryption protocols used in many cameras enabling them to eavesdrop on camera streams [8], again raising privacy concerns and creating opportunities for crime [9]. Such concerns may impede consumer confidence in, and the uptake of, the benefits the IoT promises to deliver [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, research has shown that-by taking advantage of hardware or protocol flaws-attackers can exploit man-in-the-middle attacks to intercept communications from and to wearable devices to steal personal information, invading user's privacy and exposing them to the risk of identity theft [7]. Attackers can also take advantage of the weak authentication and encryption protocols used in many cameras enabling them to eavesdrop on camera streams [8], again raising privacy concerns and creating opportunities for crime [9]. Such concerns may impede consumer confidence in, and the uptake of, the benefits the IoT promises to deliver [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in a research by Obermaier and Hutle [12] provided a practical analysis of the security and privacy of four major cloud-based video surveillance systems. They reverseengineered the security implementation and discovered several vulnerabilities in every of the tested systems.…”
Section: Related Work 21 Related Work On Building Burglary and Theftmentioning
confidence: 99%
“…Several works have shown how a potential attacker can gain accurate insights on users' activity and data. Sensitive information can be gathered by installing a Man-in-the-Middle (MitM) malware that re-transmits data [2,3], or by eavesdropping packets exchanged on a shared network channel [4]. Network engineers have thus been designing encryption strategies to prevent third party users from accessing the transmitted information (e.g., SSL/TLS).…”
Section: Introductionmentioning
confidence: 99%